Interpreting Dancing as Symbols of Freedom in Remy Sylado’s Namaku Mata Hari from Its Protagonist Personality - Noer Azisi; Andang Saehu (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2018)
This study interprets the ‘dancing’ as symbols of freedom expressed by a Dutch dancer, Mata Hari (alias Margaretha Geertruida Zelle) in Remy Sylado’s Namaku Mata Hari, a protagonist novel.  The data in this study are sentences or paragraphs containing dancing as symbols of freedom.  Those sentences or paragraphs were collected by conducting library research through reading carefully the novel Namaku Mata Hari, coding each part of the novel showing the dancing as a symbols of freedom and the role of her id, ego and super ego, classifying data into symbols proposed by Hayek’s (1960) and Hospers’ (1984) theories, and analysing the data simultaneously.  The result shows that the dancing as freedom symbols is interpreted in a lot of expressions: dancing expressing her freedom of being life, of taking back her rights, of avoiding Western aesthetic principles, of being peaceful state of mind, of finding her desire, of gaining a deep hypnotic trance, of gaining humanity instead of being prejudice of her nationality, and of avoiding Western civilization.